Community, solidarity, and belonging levels of community and their normative significance - Mason, Andrew 1959- (Cambridge University Press, 2000)
Despite the frequency with which the term 'community' is used, it is hard to find any comprehensive exploration of the nature and value of community. This book tries to remedy this omission whilst taking seriously the idea that community can be of different kinds and can exist at different levels, and that these levels and kinds may come into conflict with one another. It focuses on the question of what kind of community is valuable at the level of the state. It then explores the limits that ideals of political community place upon cultural diversity within the state, and the limits that, in turn, ideals of global community place upon the self-determination of political communities. This book will be of interest to students of political theory, philosophy and international relations
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Politik; Communities; Communities / Political aspects; Cultural pluralism; Nation-state; Internationalism; Politische Philosophie; Gemeinschaft